2021
DOI: 10.3390/molecules26164727
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antioxidant Capacity and Antimicrobial Properties of Selected Polish Grape Vinegars Obtained by Spontaneous Fermentation

Abstract: Nowadays, products of natural origin with health-promoting properties are increasingly more common. Research shows that fruit vinegars can be a source of compounds with antioxidant activity. Research on the total antioxidant capacity, total phenolic content, and antimicrobial properties against Staphylococcus aureus, Escherichia coli, and Candida albicans of grape vinegars were conducted. Moreover, gas chromatography was used to measure acetic acid content in the vinegars. The research material consisted of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Studies in this review attributed the antimicrobial activity of vinegars to the presence of acetic acid (67,71,72), but also suggest that polyphenolic compounds and the presence of other organic acids may play a role in antimicrobial activity (65)(66)(67)71). We cannot conclude from the published literature whether the activity of vinegar is entirely due to its acetic acid content or if whole vinegar is more or less effective than its acetic acid content, i.e.…”
Section: A Systematic Review Of Published Evidence For Antimicrobial ...mentioning
confidence: 81%
“…Studies in this review attributed the antimicrobial activity of vinegars to the presence of acetic acid (67,71,72), but also suggest that polyphenolic compounds and the presence of other organic acids may play a role in antimicrobial activity (65)(66)(67)71). We cannot conclude from the published literature whether the activity of vinegar is entirely due to its acetic acid content or if whole vinegar is more or less effective than its acetic acid content, i.e.…”
Section: A Systematic Review Of Published Evidence For Antimicrobial ...mentioning
confidence: 81%
“…In this study, the flora natively existing in BW was involved during spontaneous fermentation, regarded as the age-old method of homemade vinegar production. Nevertheless, the fermentation takes longer to execute compared to modern processing methods [32]. Currently, it is observed that the interest in fermented food by traditional production methods is gradually returning [33].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of DPPH free radical scavenging was also affected by organic acids, specificly, GABA, lactic acid and gallic acid (p < 0.01). The antioxidant activity of vinegars may be attributed to these present organic acids apart from acetic acid, including gallic acid, caffeic acid, syringic acid, citric acid, chlorogenic acid, tartaric acid and ferulic acid [32,59,60]. Short fatty acids, such as lactic acid and acetic acid, possess antimicrobial and nutritional benefits [58].…”
Section: Correlations Among Metabolites and Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the dominant compounds is tocopherol, which is a group of vitamin E. This compound has the potential as an antioxidant 21 . In addition, there are also acetic acid compounds that have the ability as antioxidants and antibacterial agents against Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922 and Candida albicans ATCC 10231 22 (Table 4).…”
Section: Discussionmentioning
confidence: 99%